2001
DOI: 10.1046/j.1423-0410.2001.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enterovirus viraemia in blood donors

Abstract: The prevalence of enterovirus viraemia detected in this study predicts that at least 1000 enterovirus-contaminated blood components are transfused per year in the UK. The frequency of transmission and clinical outcome after exposure to enterovirus-contaminated blood components in recipients is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
(9 reference statements)
2
25
0
Order By: Relevance
“…Conserved regions between HRV-A, -B, and -C coincided with those of HEV-A to HEV-D, enabling a combined HRV-HEV amplification method, although the incorporation of HEV and HRV-C amplification necessitated the use of separate inner sense primers; for example, HEV 5Ј UTR sequences differed from HRV at several positions in the primer-binding target ( Table 1; the bases that are different are underlined and in boldface). The sensitivity of the combined HEV-HRV PCR was compared to that of a previously described 5Ј UTR-based nested PCR previously used for the screening of clinical specimens (cerebrospinal fluid in suspected viral meningitis/encephalitis cases [19]) and surveillance samples (blood donor screening [39]) ( Table 2). On the basis of the proportion of replicates positive at each dilution, the two assays showed identical sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…Conserved regions between HRV-A, -B, and -C coincided with those of HEV-A to HEV-D, enabling a combined HRV-HEV amplification method, although the incorporation of HEV and HRV-C amplification necessitated the use of separate inner sense primers; for example, HEV 5Ј UTR sequences differed from HRV at several positions in the primer-binding target ( Table 1; the bases that are different are underlined and in boldface). The sensitivity of the combined HEV-HRV PCR was compared to that of a previously described 5Ј UTR-based nested PCR previously used for the screening of clinical specimens (cerebrospinal fluid in suspected viral meningitis/encephalitis cases [19]) and surveillance samples (blood donor screening [39]) ( Table 2). On the basis of the proportion of replicates positive at each dilution, the two assays showed identical sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…Scottish blood donor samples were obtained in a previous study, in which a highly sensitive reverse transcriptase PCR (RT-PCR) amplification method using highly conserved primers specific for the 5Ј UTR was used to screen approximately 330,000 blood donation samples in pools of 95 between 2000 and 2001 (44). Viremic donors were identified by testing cross pools and individual donations; through the use of this procedure, no pools were found that contained more than one PCR-positive component donation (44). Samples found to be positive using the 5Ј UTR RT-PCR assay were further investigated by amplification and sequencing of regions of the capsid (VP1) for serotype identification as previously described (44).…”
Section: Methodsmentioning
confidence: 99%
“…Viremic donors were identified by testing cross pools and individual donations; through the use of this procedure, no pools were found that contained more than one PCR-positive component donation (44). Samples found to be positive using the 5Ј UTR RT-PCR assay were further investigated by amplification and sequencing of regions of the capsid (VP1) for serotype identification as previously described (44). The sequence of the 251-nt region of VP1 (positions 3090 to 3341, numbered relative to the poliovirus P3/Leon/37 strain; accession number K01392) was capable of reliably identifying the enterovirus serotype in each of the blood donor samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4). Targeted amplification from stool samples, using pan-HEV primers (39), indicated that 23 of these 35 tested patients were positive for HEV infection (20), 17 of which were also identified using viral metagenomics. Other known enteric viruses observed included adenovirus, picobirnavirus, rotavirus, Aichi virus, parechovirus, and rhinovirus, as well as assorted plant viruses of the families Partitiviridae and Tobamoviridae ( Fig.…”
Section: Samplingmentioning
confidence: 99%